Preliminary assessment of habitat uses and time budget by an urban group of white-footed tamarins (Oedipomidas leucopus, Callitrichidae) (2025)
High levels of species diversity and endemism in developing countries contrast with a dramatic expansion of human populations and urban development. This poses a challenge for wildlife and their ability to adapt to transformed and fragmented habitats. In the Neotropics, tamarins and marmosets (Primates: Callitrichidae) have established populations in urbanized areas, including the White-footed tamarin in north-western Colombia, where it is prone to metabolic syndrome presumably due to nutritional issues and reduced physical activity. We conducted an exploratory analysis of habitat use and activity budget of a group of the White-footed tamarin established in an isolated forest patch in Medellín, Colombia over a 12-month period. We applied multiple linear regressions to assess 1) the seasonal variation of diet and 2) the role of landscape features on the use of the available habitat. Resting was the most dominant behavior. The diet comprised a range of animal and plant items as well as a smaller proportion of anthropogenic food. The diet diversity showed an inverse relationship with the within-month humidity variation, indicating an adaptation to seasonal changes. The use of available area was associated with tree density and abundance of key plant species that are either consumed or used as part of corridors. Our results suggest that seasonal plasticity and generalist diet habits may be favored in species adapted to urbanized areas, but food oversupply may lead to sedentarism and compromise the health of urban fauna. Strategic planting of key tree species that provide food sources and facilitate dispersal is recommended.